Leachate filtration by using low cost material / Farahdilla Ahmad Fauzy - Ahmad Fauzy, Farahdilla (Faculty Of Civil Engineering, 2006)
Filtration is a mechanism by which leachate constituents are physically trapped. Filtration efficiency depends on pore size and hydraulics gradients of the leachate. The main purpose of this Final Year Project is to remove the parameter of COD, SS, pH, conductivity, Iron (Fe) and Manganese (Mn) in leachate. This treatment is important to ensure that the values of parameter are fulfilling the Environment Quality (Sewage and Industrial Effluents) Regulation, 1979 based on maximum effluent parameter limits Standard A and B. This treatment is a pre-treatment of leachate where we use the crush stone and charcoal as a filtration media at different diameter. The sample that be used in this treatment is a leachate from landfill Idaman Bersih Sdn Bhd (IBSB) at Sg Burong. In order to fulfill the objective of this study, one of the experiment will carry on, whish using the low cost material to obtain the values of parameter COD, SS, pH, conductivity, Iron (Fe) and Manganese (Mn) of sample before(influent) and after(final effluent) treatment. Comparison between influent and final effluent parameters will be taken to evaluate the effectiveness the crush stone and charcoal as a filtration media. This medium can remove the parameters such as SS up to 80%, Conductivity up to 52% and Manganese up to 56.25%. The results show the removal a percentage is influence by detention time and size of filtration media. The removal percentages of these parameters were better for 5 hours detention time. The filtration process will be done by using the same filtration media without backwashing process.